Continuum Mechanics Through the Eighteenth and Nineteenth Centuries Historical Perspectives from John Bernoulli (1727) to Ernst Hellinger (1914) - Maugin, Gerard A. (Solid Mechanics and Its Applications,, 2014)
Conceived as a series of more or less autonomous essays, the present book critically exposes the initial developments of continuum thermo-mechanics in a post Newtonian period extending from the creative works of the Bernoullis to the First World war, i.e., roughly during first the â_oAge of reasonâ__ and next the â_oBirth of the modern worldâ__. The emphasis is rightly placed on the original contributions from the â_oContinentalâ__ scientists (the Bernoulli family, Euler, dâ_TAlembert, Lagrange, Cauchy, Piola, Duhamel, Neumann, Clebsch, Kirchhoff, Helmholtz, Saint-Venant, Boussinesq, the Cosserat brothers, Caratheodory) in competition with their British peers (Green, Kelvin, Stokes, Maxwell, Rayleigh, Love,..). It underlines the main breakthroughs as well as the secondary ones. It highlights the role of scientists who left essential prints in this history of scientific ideas. The book shows how the formidable developments that blossomed in the twentieth century (and perused in a previous book of the author in the same Springer Series: â_oContinuum Mechanics through the Twentieth Centuryâ__, Springer 2013) found rich compost in the constructive foundational achievements of the eighteenth and nineteenth centuries. The pre-WWI situation is well summarized by a thorough analysis of treatises (Appell, Hellinger) published at that time. English translations by the author of most critical texts in French or German are given to the benefit of the readers.